Adult native knee extensor mechanism ruptures. Issue 10 (October 2016) - Pengas, I.P.; Assiotis, A.; Khan, W.; Spalding, T.
Abstract: Extensor mechanism rupture is a serious event requiring prompt diagnosis and treatment. Patella fractures are reportedly six times more frequent than soft tissue injuries such as quadriceps or patella tendon ruptures. Classically quadriceps and patella tendon ruptures are seen more in males, with those over 40 predominantly suffering from quadriceps tendon ruptures, often associated with an underlying condition, whereas patella tendon ruptures are mostly associated with sport injuries and are commonly seen in the under 40s. Almost all types of extensor mechanism ruptures benefit from early management which typically involves surgery. Diagnosis can be deemed easy to make by demonstrating inability to actively extend the knee, this however can be easily overlooked and missed in a busy emergency department leading to a late diagnosis and necessitating more complex surgery. Earlier surgical intervention and rehabilitation tend to produce improved outcomes.